2020
DOI: 10.1063/5.0006311
|View full text |Cite|
|
Sign up to set email alerts
|

Two-temperature effects in Hall-MHD simulations of the HIT-SI experiment

Abstract: A two-temperature Hall-magnetohydrodynamic (Hall-MHD) model, which evolves the electron and ion temperatures separately, is implemented in the PSI-Tet 3D MHD code and used to model plasma dynamics in the Helicity Injected Torus–Steady Inductive (HIT-SI) experiment. The two-temperature model is utilized for HIT-SI simulations in both the PSI-Tet and NIMROD codes at a number of different injector frequencies in the 14.5–68.5 kHz range. At all frequencies, the NIMROD two-temperature model results in increased tor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Alongside the experimental study, a series of eXtended MagnetoHydroDynamic (xMHD) simulations spanning the parameter space were performed using the NIMROD code. 22 NIMROD has been used extensively to model both the HIT-SI [23][24][25][26] and HIT-SI3 9 devices. For simulations in this work, a zero-b Hall MHD model was used, with the application previously described in Ref.…”
Section: Non-linear Dynamic Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Alongside the experimental study, a series of eXtended MagnetoHydroDynamic (xMHD) simulations spanning the parameter space were performed using the NIMROD code. 22 NIMROD has been used extensively to model both the HIT-SI [23][24][25][26] and HIT-SI3 9 devices. For simulations in this work, a zero-b Hall MHD model was used, with the application previously described in Ref.…”
Section: Non-linear Dynamic Modelmentioning
confidence: 99%
“…6 While the simulations may capture some of the variation in current amplification, the level of disagreement seen is consistent with past results studying the importance of finite-b effects in simulations of HIT-SI and HIT-SI3. Past work 9,25,26 found that toroidal current gain has a strong dependence on the electron temperature, which sets the plasma resistivity and plasma density, which influences the magnitude of the dynamo terms that provide the majority of current drive.…”
Section: Physics Of Plasmasmentioning
confidence: 99%
“…Examples include no-slip conditions, periodic boundary conditions [10,60], mixed no-slip and periodic boundary conditions [61], and open flows in which the velocity magnitude decreases faster than the relevant surface integrals expand (e.g., two-dimensional rigid body wake flows and three-dimensional round jets) [62]. In magnetohydrodynamics, there are additional quadratic nonlinearities through ∇ × (u × B) and J × B, which are also energy-preserving with common experimental boundary conditions such as a conducting wall [63], or a balance between dissipation and actuation in a steady-state plasma device [36,64]. Notably, dissipationless Hall-MHD has four invariants; energy, cross-helicity, magnetic helicity, and generalized helicity [65], providing a wealth of potential model constraints for Hall-MHD ROMs.…”
Section: Reduced-order Modeling and The Trapping Theoremmentioning
confidence: 99%
“…For clarity of presentation and robust connection with the Galerkin literature in fluid mechanics, we present results for MHD models which are at most quadratic in nonlinearity. This includes ideal MHD, incompressible Hall-MHD, or compressible Hall-MHD with a slowly time-varying density, which together describe the dynamics of a fairly broad class of space and laboratory plasmas [27][28][29][30][31][32].…”
Section: Low-dimensional Modelsmentioning
confidence: 99%